A emergência das políticas de educação bilíngue para surdos no Brasil na racionalidade inclusiva - Morais, Mônica Zavacki de (2015)
Considering the strategic role that bilingual education policies have played in the present educational setting, in this thesis, I have problematized the ways in which the discourses about bilingual education policies in the Brazilian context have emerged as a condition for the inclusion of deaf subjects in contemporaneity. The following objectives have been established: to identify the historical and political moment in which we started investing in bilingual education policies for the deaf in Brazil; to analyze how the discourses about bilingual education for the deaf have emerged as a condition of possibility of inclusion of deaf subjects in contemporaneity; to problematize the processes of negotiation between the bilingual education policies for the deaf in Brazil and the Special Education Policy from the Inclusive Education Perspective. Two reasons justify my interest in this topic: firstly, the investment made by inclusive education policies and Brazilian deaf communities in the configuration of bilingual education policies in Brazil; secondly, the capturing movement of the discourse of bilingual education for the deaf by inclusive education policies. I have selected a set of documents of the historical files of the National Institute of Deaf Education, official documents of the Ministry of Education and documents formulated by the Brazilian deaf community. A genealogy-inspired exercise has enabled me to address the issues of provenience and emergence of the Bilingual Education Policies for the deaf in Brazil as a guiding axis to understand how the discourses about Sign language and Portuguese Language have not stemmed from an alleged chronological sequence in the history of deaf education; rather, they are intertwined with displacements and disruptions at linguistic, educational, economic and political levels. Concerning this return to the past, I have argued that, in the 18th and 19th centuries, the model of deaf subject required the ability to oralize so that the social order could be maintained, and, therefore, the subject could become useful and productive in society. Thus, a power of normalization was instituted and focused on those who were able to oralize and, hence, could be professionalized, and those who used only gestures. It is interesting to understand how the professionalization of deaf subjects was a great concern of the State. Another important point is the perception that the oralization and teaching of written Portuguese Language were conditions of possibility for the contemporary discourses about bilingual education, i.e. the acknowledgement and the importance of the Sign Language led to the understanding that deaf education was triggered by the political rationality then in effect. However, by understanding the deaf community as a linguistic minority, there are possibilities for its politicization and resistance to normalization practices, such as the inclusion of the deaf in regular school, the acknowledgement of Sign Language as an official language, and the methodologization of Sign Language in regular school. The discussions about the presence of a relationship between Sign Language and written Portuguese Language are still constant in the education of those subjects, thus causing mobilizations, tensions, and negotiations.